Botani, Metabolit Sekunder dan Bioaktivitas Bangle (Zigiber montanum) (Review) - Silalahi, Marina (Universitas Tribhuwana Tunggadewi, 2019)
The use of plants as a medicine is sometimes doubted in modern medicine because it is not considered to have sufficient evidence. Zingiber montanum or also known as bangle is a of the types in the family Zingiberaceae which is used as a medicine, but an in-depth study of secondary metabolites and their bioactivity is still limited. This article aims to reveal botany, secondary metabolites, and bioactivity Z. purpureum so that it can be used as a basis for its use and development as traditional medicine and modern medicine. Studies on articles are based on various literary sources obtained off line or online in the form of journals, books, which can be downloaded using keywords, Zingiber, Zingiber montanum, secondary metabolites and bioactivities of Z. montanum. Rhizoma Z. montamun produces flavors and can be used to replace ginger (Zingiber officinale). As a traditional medicine in Asia, Z. montanum is used as a carminative drug, a stimulant for the stomach, diarrhea, colic, and headaches. Based on the bioactivity test in vitro and in vivo Z. montanum has pharmacological effects as anti-inflammatory, antimicrobial, analgesic and obesity.